The forbidden library - Wexler, Django (Puffin Books, an imprint of Penguin Group(USA), 2015)
When her father is lost at sea shortly after meeting a very unusual visitor, Alice must go live with Uncle Geryon, a mysterious old man she's never heard of, with an impossibly massive library that holds much more than books.